Cancer-Associated Fibroblast-Derived Interleukin-8 Promotes Ovarian Cancer Cell Stemness and Malignancy Through the Notch3-Mediated Signaling - Ji, Zhaodong; Tian, Wenjuan; Gao, Wen; Zang, Rongyu; Wang, Huaying; Yang, Gong (Frontiers in Cell and Developmental Biology, 2021)
As a significant component in ovarian cancer microenvironment, cancer-associated fibroblasts (CAFs) contribute to cancer progression through interaction with cancer cells. Recent studies demonstrate that interleukin-8 (IL-8) is overexpressed in multiple cancers types and essential for tumor development. Nonetheless, the underlying mechanism that CAFs-derived-IL-8 promotes ovarian tumorigenesis is unknown. Here, we found that the high level of IL-8 secreted from CAFs could activate normal ovarian fibroblasts (NFs) through multiple signaling, and that IL-8 stimulated malignant growth of ovarian cancer cells in animals and increased the IC50 of cisplatin (CDDP) in HEY-A8 cells. Further study showed that IL-8 induced cancer cell stemness via activation of Notch3, and that high level of IL-8 in ascites was positively correlated with the expression of Notch3 in ovarian cancer tissues. Collectively, IL-8 secreted from CAFs and cancer cells promotes stemness in human ovarian cancer via the activation of the Notch3-mediated signaling, which may provide a novel strategy for ovarian cancer treatment.